Minimal Semantics and Word Sense Disambiguation - Gasparri, Luca (2016)
Emma Borg has defined semantic minimalism as the thesis that the literal content of well-formed declarative sentences is truth-evaluable, fully determined by their lexico-syntactic features, and recoverable by language users with no need to access non-linguistic information. The task of this article is threefold. First, I shall raise a criticism to Borg’s minimalism based on how speakers disambiguate homonymy. Second, I will explore some ways Borg might respond to my argument and maintain that none of them offers a conclusive reply to my case. Third, I shall suggest that in order for Borg’s minimalism to best accommodate the problem discussed in this paper, it should allow for semantically incomplete content and be converted into a claim about linguistic competence.